„Opowiadanie jest stałym bytu cieniem”. Kilka uwag o kanonie Zagłady w literaturze najnowszej - Tomczok, Marta (Narracje o Zagładzie [czasopismo zamknięte], 2015)
“Narration is the persistent shadow of existence”. Some remarks about the canon of the Shoah in the most recent literary works On the basis of abundant short‑story and novelistic material the author presents the formation of the contemporary canon of the Shoah. According to Marta Tomczok, the domination of the short story over the novelistic form constitutes a result of the dialogue of generations and its influence upon the narrative situation of the prose by Agnieszka Kłos, Sylwia Chutnik or Magdalena Tulli. And in a deeper sense, which is discernible in Czarne sezony by Michał Głowiński, it involves a departure from the fictionalisation of the Shoah in favour of an autobiographical and memoir reflection. The author perceives the causes of such a state of affairs in the influence of Sąsiedzi by Jan Tomasz Gross upon Polish literature after 2000, and the rhetoric of cruelty, which is more and more discernible in it, as well as in the separation of the historiographical and the narrative discourses, which according to the author, influence each other in the case of the contemporary narrations about the Shoah, above all in the sphere of the popular novel. Key words: canon, narration, Holocaust, story, novel